131k views
14 votes
Step by step explanation

Step by step explanation-example-1
User Sebastiaan
by
5.1k points

2 Answers

3 votes

Answer:

a) the given value is not a solution to the equation

b) the given value is a solution to the equation

c) the given value is a solution to the equation

d) the given value is not a solution to the equation

Explanation:

a) 2k + 6 = 34

2k = 34 - 6

2k = 28

k = 14 (the question states that k = 20 but that is not true, there for k = 20 is not a solution to the equation)

b)
(y)/(3) - 2 = 7


(y)/(3) = 7 + 2


(y)/(3) = 9


y = 27 (the question states also states that y = 27, therefore the given value of y is a solution to the equation)

c) 23 = 3 + 4g

4g = 23 - 3

4g = 20

g = 5 (the question states also states that g = 5, therefore the given value of g is a solution to the equation)

d)
9 = (p)/(3) - 1


(p)/(3) = 9 + 1


(p)/(3) = 10


p = 30 (the question states that p = 24 but that is not true, therefore p = 24 is not a solution to the equation)

User Cembo
by
5.1k points
8 votes

Answer:

a. no

b. yes

c. yes

d. no

Explanation:

a. 2(20)+6=34 multiply 2 by 20

40+6=34 add 40 and 6


46\\eq 34

b. 27/3-2=7 divide 27 by 3

9-2=7 subtract

7=7

c. 23=3+4(5) multiply 4 and 5

23=3+20 add 3 and 20

23=23

d. 9=24/3-1 divide 24 by 3

9=8-1 subtract 8 and 1


9\\eq 7

User Tgolisch
by
5.6k points